STUDY ON TENSILE MECHANICAL BEHAVIOR OF X-TYPE RE-ENTRANT HONEYCOMB STRUCTURE - WANG Liang; LIU HaiTao (Jixie qiangdu, 2020)
Based on the re-entrant mechanism,the microstructure of the star and the re-entrant hexagon is combined. This paper designs a new re-entrant honeycomb structure model（X-shaped structure）. For the structure model,the relative density is given to achieve the purpose of weight reduction. The axial tensile mechanical behavior of the structure is studied by finite element software ABAQUS. Tip re-entrant angle,the variation of cell wall thickness,external angle and material properties on effective elastic modulus and Poisson’s ratio are obtained. The numerical results show that the important factor of affecting the structure is the external angle. With the increase of the external angle,the effective elastic modulus and Poisson’s ratio will increase. When the external angle reaches about 67°,the structure is zero Poisson’s ratio structure. Meanwhile,with the increase of the cell wall thickness,the negative Poisson’s ratio effect of the structure is more obvious,and the effective elastic modulus is also larger. When the tip angle is smaller,the negative Poisson’s ratio effect is stronger. The results can be provided a new reference for the optimization design of the new negative Poisson structure.